Malignant peripheral nerve sheath tumour of the renal parenchyma presenting as a fast growing atypical renal cyst - Ouellet, Simon; Doueik, Alexandre; Sabbagh, Robert (Canadian Urological Association Journal, 2013)
Malignant peripheral nerve sheath tumours (MPNST) of the kidney are very rare, with only 3 cases reported in the English and French literature. However, we report the first case of fast growing atypical renal cyst where a magnetic resonance imaging was an interesting adjunct to the computed tomography scan in imaging this rare tumour.